2016
DOI: 10.1152/jn.00066.2015
|View full text |Cite
|
Sign up to set email alerts
|

Delayed feedback during sensorimotor learning selectively disrupts adaptation but not strategy use

Abstract: Brudner SN, Kethidi N, Graeupner D, Ivry RB, Taylor JA. Delayed feedback during sensorimotor learning selectively disrupts adaptation but not strategy use. J Neurophysiol 115: 1499 -1511, 2016. First published January 20, 2016 doi:10.1152/jn.00066.2015.-In sensorimotor adaptation tasks, feedback delays can cause significant reductions in the rate of learning. This constraint is puzzling given that many skilled behaviors have inherently long delays (e.g., hitting a golf ball). One difference in these task doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
154
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(170 citation statements)
references
References 57 publications
13
154
3
Order By: Relevance
“…Overall, our results provide further support for the general consensus that explicit re-aiming is an essential component of sensorimotor learning in a visuomotor rotation task and may be responsible for a variety of motor learning behaviors thought to be largely implicit (Heuer and Hegele, 2008; Hegele and Heuer, 2010; Taylor et al, 2014; Bond and Taylor, 2015; McDougle et al, 2015; Morehead et al, 2015; Brudner et al, 2016; Day et al, 2016; Poh et al, 2016). There are two primary implications of our results.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Overall, our results provide further support for the general consensus that explicit re-aiming is an essential component of sensorimotor learning in a visuomotor rotation task and may be responsible for a variety of motor learning behaviors thought to be largely implicit (Heuer and Hegele, 2008; Hegele and Heuer, 2010; Taylor et al, 2014; Bond and Taylor, 2015; McDougle et al, 2015; Morehead et al, 2015; Brudner et al, 2016; Day et al, 2016; Poh et al, 2016). There are two primary implications of our results.…”
Section: Discussionsupporting
confidence: 79%
“…However, this interpretation stands in contrast to a recent series of findings demonstrating that explicitly accessible re-aiming processes constitute the majority of learning (Heuer and Hegele, 2008; Hegele and Heuer, 2010; Taylor et al, 2014; Bond and Taylor, 2015; McDougle et al, 2015; Brudner et al, 2016; Day et al, 2016; Poh et al, 2016). We previously found that explicit re-aiming composed the flexible component of performance across a range of rotation magnitudes while implicit recalibration exhibited a stereotyped response (Bond and Taylor, 2015).…”
Section: Introductioncontrasting
confidence: 86%
“…Consequently, task differences in the involvement of implicit vs. explicit learning mechanisms may play a role in the differential effects of sensory delays on speech and limb adaptation. This suggestion is consistent with recent work showing that, in upper limb motor learning, feedback delays negatively affect implicit learning but not explicit strategy selection (Brudner et al 2016;McDougle and Taylor 2019;Schween and Hegele 2017). It follows, then, that feedback delays may have only a relatively minor impact on visuomotor reach adaptation because it is characterized by a small implicit component and a large explicit component, at least in the case of an abruptly introduced perturbation (Anguera et al 2010;Fernandez-Ruiz et al 2011;McDougle et al 2016;Taylor et al 2014) or a gradually introduced perturbation with reward feedback (Holland et al 2018).…”
Section: Introductionsupporting
confidence: 90%
“…Indeed, several studies on speech sensorimotor learning have demonstrated that subjects are unaware that they made any changes in their speech output in the presence of the perturbation, and that there is no difference in the extent of adaptation when subjects are instructed to ignore the feedback or to avoid compensating for the perturbation (Keough et al 2013;Kim and Max 2020;Munhall et al 2003). In light of recent findings that delayed feedback may negatively affect implicit learning without much impact on explicit strategy selection (Brudner et al 2016;McDougle and Taylor 2019;Schween and Hegele 2017), speech auditory-motor learning may be resistant to the benefits of prior delay habituation due to being largely implicit in nature (Keough et al 2013;Kim and Max 2020;Munhall et al 2003). By purposefully designing new speech auditory-motor learning paradigms that depend to varying degrees on implicit vs. explicit learning, future studies might be able to directly test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, supervised learning is a hallmark of cerebellar function, driven by the sensory prediction error signal [42]. Notably, this signal is temporally constrained; slight delays in the delivery of an error signal markedly reduce the rate of learning [162, 163], a constraint that is much weaker in basal ganglia-dependent, reinforcement learning [164]. The exquisite temporal precision of cerebellar processing may be a key characteristic to differentiate cerebellar processing from that in the cerebral cortex [165].…”
Section: Constraints On Cerebellar Prediction and Error Processing Inmentioning
confidence: 99%